Internet Use for Health-Care Information by Subjects With COPD. - Delgado, Cionéia K.; Gazzotti, Mariana R.; Santoro, Ilka L.; Carvalho, Andrea K.; Jardim, José R.; Nascimento, Oliver A. (Respiratory Care, 2015)
BACKGROUND: Although the internet is an important tool for entertainment, work, learning, shopping, and communication, it is also a possible source for information on health and disease. The aim of this study was to evaluate the proportion of subjects with COPD in Sao Paulo, Brazil, who use the internet to obtain information about their disease. METHODS: Subjects (N = 382) with COPD answered a 17-question survey, including information regarding computer use, internet access, and searching for sites on COPD. Our sample was distributed according to the socioeconomic levels of the Brazilian population (low, 17.8%; medium, 66.5%; and high, 15.7%). RESULTS: Most of the subjects in the sample were male (62.6%), with a mean age of 67.0 ± 9.9 y. According to Global Initiative for Chronic Obstructive Lung Disease (GOLD) stages, 74.3% of the subjects were in stage II or III. In addition, 51.6% of the subjects had a computer, 49.7% accessed the internet, and 13.9% used it to search for information about COPD. The internet was predominantly accessed by male (70.3%) and younger (64.6 ± 9.5 y of age) subjects compared with female (29.7%, P = .04) and older (67.5 ± 9.6 y of age, P < .007) subjects. Searching for information about COPD on the internet was associated with having a computer (5.9-fold), Medical Research Council dyspnea level 1 (5.3-fold), and high social class (8.4-fold). The search for information on COPD was not influenced by GOLD staging. CONCLUSIONS: A low percentage of subjects with COPD in Sao Paulo use the internet as a tool to obtain information about their disease. This search is associated with having a computer, low dyspnea score, and high socioeconomic level.